†Neilpeartia ceratoi, gen. et sp. nov., a new frogfish from the Eocene of Bolca, Italy. Issue 2 (3rd March 2020) - Carnevale, Giorgio; Pietsch, Theodore W.; Bonde, Niels; Leal, Maria E. C.; Marramà, Giuseppe
ABSTRACT: † Neilpeartia ceratoi, gen. et sp. nov., a new antennariid frogfish, is described based on a single, well-preserved, articulated specimen from the Ypresian of Bolca, Italy. The morpho-anatomical analysis of this nicely preserved fossil reveals a series of features that unambiguously support its recognition as a new member of the lophiiform family Antennariidae, including body extensively covered with tiny, close-set, bifurcated dermal spinules, illicium considerably elongate and broadly spinulose in its lower portion, bulbous esca absent, endopterygoid, epural, and caudal peduncle present; caudal fin with nine branched rays, 19 vertebrae, 13 dorsal-fin rays, eight anal-fin rays, nine pectoral-fin rays, and five bifurcated pelvic-fin rays. † Neilpeartia, gen. nov., is assigned to the subfamily Antennariinae, and seems to form a sister pair with the extant genus Fowlerichthys, which in turn represents the sister clade to all the other antennariine taxa. Consequently, † Neilpeartia ceratoi, gen. et sp. nov., should be regarded as the oldest known unquestionable evidence of crown antennariids in the fossil record. Paleoecological and evolutionary implications are also discussed. http://zoobank.org/urn:lsid:zoobank.org:pub:6EDE89ED-42EF-4E3C-9EA8-C217B9FC87D4 Citation for this article: Carnevale, G., T. W. Pietsch, N. Bonde, M. E. C. Leal, and G. Marramà. 2020. † Neilpeartia ceratoi, gen. et sp. nov., a new frogfish from the Eocene of Bolca, Italy. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2020.1778711 .